Management of Learning Based Rough Motoric & Memory Ability A Site Study at SDN Kedungsari 3 Magelang - Astuti, Subiyanti Ning (2012)
Objective of the research are to describe (1) characteristics of teachers in the learning efforts to improve gross motor skills of children at SDN Kedungsari 3 Magelang. (2) characteristic of the efforts of teachers in learning to improve memory in children SDN Kedungsari 3 Magelang. It is a qualitative research using ethnography design. The research was conducted at SDN Kedungsari 3 Magelang. The main subject of research is the principal and teachers at SDN Kedungsari 3 Magelang. The method of collecting data use interviews, observation, and documentation. Analysis of data taken is the reduction of data, presentation of data and the inferences or verification. Test the validity of the data using the credibility, transferability, dependability and conformability. The results of this research show that (1) Teachers SDN Kedungsari 3 Magelang made various efforts to improve gross motor skills of students. Teachers integrate the material gross motor skills of students in some subjects such as physical health Education, School Health Unit, Mathematical and Physical Sciences, or local content. In order for students to freely in performing gross motor movements, teachers do outside of class learning the field. All facilities have been prepared as a board plank, a ball, a sandbox, rope to jump rope games and other supplies. Teachers provide varied movements such as movement of locomotors, non locomotors, and manipulative. The material provided in accordance with the vision of SDN Kedungsari 3 Magelang including physical, mental, and moral. (2) Teachers of SDN Kedungsari 3 Magelang made various efforts to improve memory learning in students. Teachers are very concerned delivery of content provided by coherent, concrete and varied. In addition, the teacher repeating the material in a way pre test and also memorize. Students receive learning materials provided teachers through educational games such as action games, finger games and also sings. The teacher asks the submitted materials are recorded so students who are less good in short-term memory can reread the material that has been delivered. The material is managed in this way, easy to understand students and enable students to remember the material. For strengthening the memory of students, teachers conduct activities such as creating a glossary of habituation and provide motivation to students.